EFFECTIVENESS OF COMBINATION OF BITTER GOURD (Momordica charantia L.) AND GARLIC (Allium sativum L.) EXTRACT ON MALE WHITE MICE (Mus muscullus) AS APHRODISIAC - Alfiraza, Ery Nourika; Listina, Osie; Gautama, Tomy Sugiarto (Jurnal FARMASIMED (JFM), 2022)
Aphrodisiac is a material that used to increase libido or sexual desire. The purpose of this study was to determine the effect of aphrodisiac on bitter melon fruit (Momordica charantia L.) and garlic (Allium sativum L.) in male white mice (Mus musculus L.) and at what concentration the combination of bitter melon and garlic had the best aphrodisiac effect. Bitter melon powder and garlic were macerated with 70% ethanol for 4 x 24 hours. In this study, ICC (Introduction, Climbing, Coitus) method was used in 25 male mice divided into 5 groups. Group I as negative control was given aquadest, group II was given a single dose of bitter melon, group III a single dose of garlic, Group IV, and Group V were given a combination of bitter melon extract and garlic with ½ combination 980 mg/kg body weight: 150mg /kg body weight, Group IV, and V were given a combination of bitter melon extract and garlic with 1 combination 1960 mg/kg body weight: 300 mg/kg body weight. Each group was given oral test materials, group I, II, III, IV, and V was given extracts according to the dose for 2 hours. Then those observed and calculated the number of Introduction, Climbing, and Coitus. The results showed that the combination of bitter melon extract and garlic group V (1960 mg/kg body weight: 300 mg/kg body weight) had the best aphrodisiac activity compared to other extract combination activities, and all extract combinations showed significantly different aphrodisiac effects.